2022
DOI: 10.1128/spectrum.00546-22
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptococcus pneumoniae Macrolide Resistance and Its Mechanism in Northeast China over a 20-Year Period

Abstract: This study presents a retrospective analysis using 1,240 clinical erythromycin-resistant Streptococcus pneumoniae (ERSP) isolates collected in northeastern China between January 2000 and December 2019. The serotype distribution, corresponding vaccine coverage, as well as resistance phenotypes, genes, and mechanisms to macrolide and tetracycline of these isolates were systematically described, analyzed, and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The erm (B) gene-mediated resistance in pneumococci gives high-level resistance (MLS B phenotype), with MIC values typically ≥ 64 μg/mL. In contrast, the efflux pump (M phenotype) encoded by the mef (A) gene confers a low-level resistance, with MIC usually 1 μg/mL–32 μg/mL ( 9 , 17 , 18 ). Similarly, in this study, among the 30 erythromycin-resistant pneumococci, isolates that carry the erm (B) gene alone or both erm (B) and mef (A) genes showed higher MICs, ranging from 2 μg/mL to > 256 μg/mL, with MIC 90 values for erm (B) gene being > 256 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The erm (B) gene-mediated resistance in pneumococci gives high-level resistance (MLS B phenotype), with MIC values typically ≥ 64 μg/mL. In contrast, the efflux pump (M phenotype) encoded by the mef (A) gene confers a low-level resistance, with MIC usually 1 μg/mL–32 μg/mL ( 9 , 17 , 18 ). Similarly, in this study, among the 30 erythromycin-resistant pneumococci, isolates that carry the erm (B) gene alone or both erm (B) and mef (A) genes showed higher MICs, ranging from 2 μg/mL to > 256 μg/mL, with MIC 90 values for erm (B) gene being > 256 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 263 isolates by MLST, and the results showed that ST271, ST320, ST90 and ST876 were the most prevalent STs in Southwest China, similar to other parts in China ( Wang X. et al, 2020 ; Zhou et al, 2022 ) but different from those in other countries, such as northern Russia ( Vorobieva S Jensen et al, 2020 ) and Latin America ( Moreno et al, 2020 ). The present study further revealed 38 novel STs, which accounted for 35.51% of all isolates (43/263), strongly indicating the global diversity of S. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China that collected 993 strains of S. pneumoniae up to 2017 showed that the non-susceptibility rate of IPD strains to penicillin reached 22.4%, which was significantly higher than that of the non-invasive strains ( Yan et al., 2021 ). However, another pneumococcal epidemiological study collected 300 invasive pneumococci from 2010 to 2015 and reported a very low PNSP rate (4.3%) ( Zhou et al., 2022b ). Later, the same group performed a deeper analysis of PBPs using conventional PCR and showed that the PBP site substitutions in PNSP strains matched our findings of non-susceptible PBP, which were distributed mostly in prevalent clones.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these inconsistent results might be due to MIC value interpretation, sample collection time periods, and regional differences. Macrolide and tetracycline resistance was maintained at high levels in both invasive and non-invasive pneumococci, which is mediated by the national distribution of ermB and tetM in China ( Zhou et al., 2022b ), indicating the limited clinical value of such drugs in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation